2020
DOI: 10.1080/13603116.2020.1735543
|View full text |Cite
|
Sign up to set email alerts
|

Catering for ‘very different kids’: distance education teachers’ understandings of and strategies for student engagement

Abstract: Compulsory distance education has always sought to be inclusive, providing educational opportunities for K-12 students unable to attend mainstream, face-to-face schools for medical, geographical, or personal reasons. However, how to effectively engage these diverse learners has remained a perpetual challenge, with a need for further investigation into the nature of student engagement with compulsory school distance contexts and how teachers can best support it. This qualitative study used focus groups (n = 2 g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
44
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(49 citation statements)
references
References 20 publications
5
44
0
Order By: Relevance
“…One of the other critical changes in independent learning is that how to enable students to decide what online/offline sources to select and use (Harris et al, 2020 ). It was found that independent learning positively impacts the motivation, performance and self-efficacy of students (Boyer et al, 2013 ).…”
Section: Literature Reviewmentioning
confidence: 99%
“…One of the other critical changes in independent learning is that how to enable students to decide what online/offline sources to select and use (Harris et al, 2020 ). It was found that independent learning positively impacts the motivation, performance and self-efficacy of students (Boyer et al, 2013 ).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Asking students to consider how they learn in online spaces SRL requires learners to think about how they learn (Harris et al, 2020). Online teachers have focused on helping students understand what it means to learn online in contrast to learning in a traditional setting (Rice and Carter, 2016).…”
Section: Cognition and Structured Learningmentioning
confidence: 99%
“…This might require assistance in problematizing thinking about ideas such as, "online learning is going to be easier than traditional learning because I can do it at home." Alongside providing information about cognition and learning online, teachers have developed questioning strategies common in traditional literacy instruction where learners generate questions, decide what online sources to use or what search terms would be helpful, do the searching and then report (Harris et al, 2020). The assigned reports do not just include responses, but narrations of how responses were achieved.…”
Section: Cognition and Structured Learningmentioning
confidence: 99%
“…Affordances in an educational setting, and especially in the virtual classroom can be understood through the specifics of educational affordances. In a recent study by Harris et al [22] , they provide empirical evidence about how one school's distance education teachers define and support engagement. On a similar note, a study by Ames et al [2] explores teachers’ perspectives regarding their use of technological tools to support their students’ learning via focus groups.…”
Section: Theoretical Framingmentioning
confidence: 99%